Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 1 - Sections 1.2-1.3 - Integrated Review - Algebraic Expressions and Operations on Whole Numbers: 12



Work Step by Step

$8-6[\sqrt[3] 8(-2)+\sqrt 4(-5)]=8-6[(\sqrt[3] 8\times-2)+(\sqrt 4\times-5)]=8-6[(2\times-2)+(2\times-5)]$ To simplify the expression, first perform the operations within parentheses. $8-6[(2\times-2)+(2\times-5)]=8-6[(-4)+(-10)]$ Next, perform the operation in brackets. $8-6[-(4+10)]=8-6[-14]$ Finally, perform the remaining operations. $8-(6\times-14)=8-(-84)=8+84=92$ Notes: We know that $\sqrt[3] 8=2$, because $2^{3}=2\times2\times2=8$ and that $\sqrt 4=2$, because $2^{2}=2\times2=4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.